2022
DOI: 10.1155/2022/7745873
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy of Dapagliflozin Combined with Lifestyle Intervention in Obesity Control

Abstract: Objective. To explore the best treatment of obesity in middle and old age. Methods. 80 obese patients in our hospital from January 2020 to December 2021 were randomly divided into the control group and the intervention group according to the numerical table method. The control group was treated with lifestyle intervention, while the intervention group was treated with dapagliflozin combined with lifestyle intervention. The effects of body weight, body mass index (BMI), waist circumference, and blood lipids (LD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…There was no significant difference in Becks Anxiety Inventory (BAI) changes, but subjects had low anxiety at baseline (BAI < 10 at baseline in all treatment arms). A second RCT by Dai and colleagues, 102 primarily studying weight loss with SGLT2 inhibitor dapagliflozin, included the 2018 Revised Anxiety and Depression Scale as a secondary end point. While the authors reported improvements in depression in both arms of the study, all patients in the intervention arm who met enrollment criteria for depression no longer met full criteria at the end point.…”
mentioning
confidence: 99%
“…There was no significant difference in Becks Anxiety Inventory (BAI) changes, but subjects had low anxiety at baseline (BAI < 10 at baseline in all treatment arms). A second RCT by Dai and colleagues, 102 primarily studying weight loss with SGLT2 inhibitor dapagliflozin, included the 2018 Revised Anxiety and Depression Scale as a secondary end point. While the authors reported improvements in depression in both arms of the study, all patients in the intervention arm who met enrollment criteria for depression no longer met full criteria at the end point.…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi, as publisher, following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of systematic manipulation of the publication and peer-review process.…”
mentioning
confidence: 99%